2018
DOI: 10.2337/dc19-s006
|View full text |Cite
|
Sign up to set email alerts
|

6. Glycemic Targets: Standards of Medical Care in Diabetes—2019

Abstract: The American Diabetes Association (ADA) "Standards of Medical Care in Diabetes" includes ADA's current clinical practice recommendations and is intended to provide the components of diabetes care, general treatment goals and guidelines, and tools to evaluate quality of care. Members of the ADA Professional Practice Committee, a multidisciplinary expert committee, are responsible for updating the Standards of Care annually, or more frequently as warranted. For a detailed description of ADA standards, statements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
224
2
28

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 580 publications
(257 citation statements)
references
References 62 publications
3
224
2
28
Order By: Relevance
“…This condition can consequently trigger cardiac arrhythmia, vasoconstriction, thrombogenicity, vascular inflammation, and vasoconstriction, leading to cardiovascular event or mortality [23]. Although the optimal range for fasting blood glucose associated with lower risk, as suggested in our study (95-124 mg/dL), might be narrower than that suggested by the global guideline, it overlaps with the general target range of fasting glucose (90-130 mg/dL) recommended by a global diabetes guideline for older adults with diabetes [24].…”
Section: Discussioncontrasting
confidence: 47%
“…This condition can consequently trigger cardiac arrhythmia, vasoconstriction, thrombogenicity, vascular inflammation, and vasoconstriction, leading to cardiovascular event or mortality [23]. Although the optimal range for fasting blood glucose associated with lower risk, as suggested in our study (95-124 mg/dL), might be narrower than that suggested by the global guideline, it overlaps with the general target range of fasting glucose (90-130 mg/dL) recommended by a global diabetes guideline for older adults with diabetes [24].…”
Section: Discussioncontrasting
confidence: 47%
“…Achieving and maintaining good glycemic control (defined as an HBA1c <7.0%) is one of the primary requirements to reduce diabetes related complications. [13,14]. It is also important to take into consideration that while the whole world is struggling to contain this deadly viral illness, focus on the co-morbidities facilitating the viral-related morbidities and mortality cannot be compromised.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is said to be uncontrolled when the blood glucose levels/glycosylated hemoglobin levels are not within the targets specified for that particular patient at a given time. HbA1c <7.0%, pre-prandial capillary plasma glucose of 80-130 mg/dl and peak postprandial capillary plasma glucose <180 mg/dl are considered as the glycemic targets for non-pregnant adults with diabetes by ADA recommendations [6]. Despite of the increasing therapeutic options for management of diabetes, inability to achieve good glycemic control remains the greatest challenge for the medical fraternity.…”
Section: Discussionmentioning
confidence: 99%